Doctors' use of mobile devices in the clinical setting: a mixed methods study. Issue 3 (March 2017) - Nerminathan, Arany; Harrison, Amanda; Phelps, Megan; Scott, Karen M.; Alexander, Shirley
Abstract : Background: Mobile device use has become almost ubiquitous in daily life and therefore includes use by doctors in clinical settings. There has been little study as to the patterns of use and impact this has on doctors in the workplace and how negatively or positively it impacts at the point of care. Aim: To explore how doctors use mobile devices in the clinical setting and understand drivers for use. Methods: A mixed methods study was used with doctors in a paediatric and adult teaching hospital in 2013. A paper‐based survey examined mobile device usage data by doctors in the clinical setting. Focus groups explored doctors' reasons for using or refraining from using mobile devices in the clinical setting, and their attitudes about others' use. Results: The survey, completed by 109 doctors, showed that 91% owned a smartphone and 88% used their mobile devices frequently in the clinical setting. Trainees were more likely than consultants to use their mobile devices for learning and accessing information related to patient care, as well as for personal communication unrelated to work. Focus group data highlighted a range of factors that influenced doctors to use personal mobile devices in the clinical setting, including convenience for medical photography, and factors that limited use. Distraction in the clinical setting due to use of mobile devices was a key issue. Personal experience and confidence in using mobile devices affected their use, and was guided by role modelling and expectations within a medical team. Conclusion: Doctors use mobile devices to enhance efficiency in the workplace. In the current environment, doctors are making their own decisions based on balancing the risks and benefits of using mobile devices in the clinical setting. There is a need for guidelines around acceptable and ethical use that is patient‐centred and that respects patient privacy.